Bound states of two-dimensional magnetoexcitons taking into account the Rashba spin–orbit coupling - Moskalenko Sveatoslav (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2020)
Molecular-type bound states of two-dimensional (2D) magnetoexcitons supplementarily subjected to the action of an external electric field perpendicular to the layer and parallel to a strong magnetic field are studied. The electron and hole wave functions have different numbers of the Landau quantization levels for different spin projections. The Rashba spin–orbit coupling (RSOC) is characterized by first-order chirality terms for electrons and third-order chirality terms for heavy holes in GaAs-type quantum wells. In this case, the external electric field gives rise to the nonparabolic dispersion law of heavy holes and a nonmonotonous dependence of their energy levels on the magnetic field strength. The spinor-type wave functions of electrons and holes for their lowest energy levels are used to construct the one- and two-magnetoexciton wave functions to determine their normalization conditions, and deduce the Hamiltonian of the Coulomb electron– electron interaction in the presence of the RSOC. It contains electron and hole imprint factors, the difference of which determines the affinities of the electron–hole pairs to interact between themselves. The average value of the Coulomb interaction Hamiltonian makes it possible to calculate the mean energy value per two pairs forming the molecule versus parameter α of the wave function, which determines the relative motion of two magnetoexcitons in the frame of the bound state. The next numerical calculations will show whether the stable bound state of the molecular type or the metastable bound state does exist.Au fost cercetate stările legate de tip molecular ale magnetoexcitonilor bi-dimensionali (2D) supuși suplimentar acțiunii câmpului electric extern perpendicular pe strat și paralel cu câmpul magnetic puternic. Funcțiile de undă asociate electronilor și golurilor au numere diferite ale nivelelor de cuantificare Landau pentru diferite proiecții de spin. Cuplarea spin-orbită de tip Rashba (RSOC) se caracterizează prin termeni de chiralitate de prim ordin pentru electroni și prin termeni de chiralitate de ordinul al treilea pentru golurile grele din gropile cuantice de tip GaAs. În acest caz, câmpul electric extern provoacă apariția dispersiei non-parabolice a golurilor grele și dependența non-monotonă a nivelelor de сuantificare de forța câmpului magnetic. Pentru a construi funcțiile de undă ale excitonului magnetic și ale bimagnetoexcitonului, pentru a determina condițiile de normalizare ale acestora și pentru a deduce Hamiltonianul interacțiunii Coulombiene electron-electron în prezența RSOC, au fost selectate funcțiile de undă de tip spinor ale celor mai mici nivele energetice ale electronilor și golurilor. Ele conțin factori de imprimare ale electronilor și a golurilor, a căror diferență determină afinitățile perechilor e-h să interacționeze între ele. Valoarea medie a Hamiltonianului interacțiunii Coulombiene permite calcularea valorii medii a energiei a două perechi care formează molecula în dependență de parametrul funcției de undă α , care determină mișcarea relativă a doi magnetoexcitoni în cadrul stării legate. Următoarele calcule numerice vor arăta dacă există starea legată stabilă de tip molecular sau starea legată metastabilă.